The effect of lavender oil on serum testosterone levels and epididymal sperm characteristics of formaldehyde treated male rats - Kose, E.; Sarsilmaz, M.; Meydan, S.; Sonmez, M.; Kus, I.; Kavakli, A. (Verduci Publisher, 2011)
Background and Objectivies: In this study, the harmful effects of formaldehyde (FA) on serum testosterone levels and epididymal sperm characteristics were investigated. In addition, possible protective effect of lavender oil was evaluated. Materials and Methods: For this purpose, 21 adult male Wistar-Albino rats were used. The rats of group I was used as control group. The rats of group II were exposed FA (10 ppm/1 hour) for 35 days. The rats of group III inhaleted lavender oil (1 ml/1 hour) with FA. Results: While the testosterone levels, the epididymal sperm concentration and the progressive sperm motility were significantly decreased, the abnormal sperm rate was significantly increased in FA treated group when compared to control group. However, in group III, the epididymal sperm concentration and the progressive sperm motility were significantly increased, the abnormal sperm rate was significantly decreased in comparison with the FA treated group. Conclusion: It can be expressed that serious damages occured via formaldehyde exposure in reproductive system and that the lavender oil had protective effects against these damages.
Keywords: Formaldehyde; Epididymis; Lavender oil; Testosterone; Rat